Tooth loss in Brazil: analysis of the 2010 Brazilian Oral Health Survey - Peres, Marco Aurelio; Barbato, Paulo Roberto; Reis, Sandra Cristina Guimaraes Bahia; Freitas, Claudia Helena Soares de Morais; Antunes, Jose Leopoldo Ferreira (Revista de Saúde Pública, 2013)
OBJECTIVE: To estimate the mean number of missing teeth, lack of functional dentition and total tooth loss (edentulism) among adolescents, adults and the elderly in Brazil, comparing the results with those of 2003. METHODS: Data from 5,445 adolescents aged 15-19, 9,779 adults aged 35-44 and 7,619 elderly individuals aged 65-74, participants in the Brazilian Oral Health Survey (SBBrasil) 2010, were analyzed. The mean missing teeth, proportion of lack of functional dentition (< 21 natural teeth) and proportion of edentulism (total tooth loss) were estimated for each age group, each state Capital and each macro region. Multivariable logistic regression (tooth loss) and Poisson (absence of functional dentition and edentulism) analyses were performed in order to identify socioeconomic factors and demographic characteristics associated with each outcome. RESULTS: The prevalence of tooth loss among adolescents was 17.4% (38.9% in 2002-03) ranging from 8.1% among those earning higher income to almost 30% among those with less schooling. Among adolescents, females, those with black or brown skin and those with the lowest levels of income and schooling had a higher prevalence of tooth loss. Lack of functional dentition affected nearly ¼ of adults, it was higher among women, among those with black and brown skin and among those with the lowest levels of income and schooling. Mean missing teeth in adults decreased from 13.5 in 2002-03 to 7.4 in 2010. More than half of elderly is edentulous (similar to the 2002-03 findings); higher prevalence of edentulism was found among women and those with the lowest levels of income and schooling. Among adolescents the mean missing teeth ranged from 0.1 (in Curitiba, South Brazil and Vitória, Southeast Brazil) to 1.2 (in the North countryside). Among adults the lowest mean missing teeth was found in Vitória (4.2) and the highest in Rio Branco, North Brazil (13.6). CONCLUSIONS: A remarkable reduction in tooth loss among adolescents and adults was identified between 2010 and 2003. Among the elderly, tooth loss figure remained the same. In spite of important achievements in tooth loss figures, social and regional inequalities persist.